Gerard Walschap, Multivariable Calculs and Differential Geometry, Walter de Gruyter (De Gruyter Graduate), 2015, ix+355 pages, Paperback, ISBN 978-3-11- 036949-6. - BLAGA, Paul A. (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The book under review is a rigorous introduction to differential geometry (mainly of hypersurfaces in a Euclidean space) based on a solid foundation of calculus and linear algebra.